Association of RNA polymerase having increased Km for ATP and UTP with hyperexpression of the pyrB and pyrE genes of Salmonella typhimurium. - Jensen, K F (1986)
We investigated the transcription kinetics of RNA polymerase from an rpoBC mutant of Salmonella typhimurium which showed highly elevated, constitutive expression of the pyrB and pyrE genes as well as an increased cellular pool of UTP. When bacterial cultures containing an F' lac+ episome were induced for lac operon expression, the first active molecules of beta-galactosidase were formed with a delay of 73 +/- 3 s in rpo+ cells. The corresponding time was 104 to 125 s for cells carrying the rpoBC allele, indicating that this mutation causes a reduced RNA chain growth rate. In vitro the purified mutant RNA polymerase elongated transcripts of both T7 DNA and synthetic templates more slowly than the parental enzyme at a given concentration of nucleoside triphosphates. This defect was found to result from four- to sixfold-higher Km values for the saturation of the elongation site by ATP and UTP. The saturation kinetics of the RNA chain initiation step also seemed to be affected. The maximal elongation rate and Km for GTP and CTP were less influenced by the rpoBC mutation. Open complex formation at the promoters of T7 DNA and termination of the 7,100-nucleotide transcript showed no significant difference between the parental and mutant enzymes. Together with the phenotype of the rpoBC mutant, these results indicate that expression of pyrB and pyrE is regulated by the mRNA chain growth rate, which is controlled by the cellular UTP pool. The rate of gene expression is high when the saturation of RNA polymerase with UTP is low and vice versa.